Chemoselective dithioacetalization of aldehydes using silica sulfuric acid as a reusable catalyst - Pore, D. M.; Desai, Uday V.; Mane, R. B.; Wadgaonkar, P. P. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2006)
Silica sulfuric acid has been found to be an efficient and reusable catalyst for chemoselective dithioacetalization of aldehydes over ketones, in excellent yields.
Keywords: Chemoselective; dithioacetalization; silica sulfuric acid

Efficient deprotection of dithioacetals to carbonyls using Oxone-KBr in aqueous acetonitrile - Desai, Uday V.; Pore, D. M.; Tamhankar, B. V.; Jadhav, Sushilkumar A.; Wadgaonkar, P. P. (Tetrahedron Letters, 2006)
A simple and efficient method has been developed for the chemoselective dethioacetalization of dithioacetals to aldehydes and ketones using Oxone-KBr in aqueous acetonitrile at room temperature. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: deprotection; dethioacetalization; Oxone

Efficient, solvent-free method for the chemoselective synthesis of acylals from aldehydes and their deprotection catalyzed by silica sulfuric acid as a reusable solid acid catalyst - Desai, Uday V.; Thopate, T. S.; Pore, D. M.; Wadgaonkar, P. P. (Catalysis Communications, 2006)
An efficient method has been developed for the chemoselective synthesis of acylals from aldehydes and acetic anhydride in the presence of silica sulfuric acid as a reusable solid acid catalyst under solvent-free conditions. Ketones are found to remain unaffected under the reaction conditions. The deprotection of acylals has also been achieved using SSA in methanol medium. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Acylals; aldehydes; Chemoselective; protection and deprotection silica sulfuric acid

Potassium phosphate or silica sulfuric acid catalyzed conjugate addition of thiols to alpha,beta-unsaturated ketones at room temperature under solvent-free conditions - Pore, D. M.; Soudagar, M. S.; Desai, Uday V.; Thopate, T. S.; Wadagaonkar, P. P. (Tetrahedron Letters, 2006)
Potassium phosphate and silica sulfuric acid have been found to be useful and highly efficient catalysts for conjugate addition of thiols to alpha,beta-unsaturated ketones under solvent-free conditions, at room temperature. Silica sulfuric acid (SSA) was found to be suitable for electron-deficient enones while potassium phosphate was found to effect thia-Michael addition with both, electron-deficient as well as electron-rich conjugated ketones. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: alpha; beta-unsaturated ketones; chalcones; conjugated enones; Michael addition; Potassium phosphate; silica sulfuric acid; thiols

Anhydrous magnesium sulfate mediated solvent-free synthesis of dihydropyrimidin-2(1H)-ones at ambient temperature - Pore, D. M.; Desai, Uday V.; Thopate, T. S.; Wadgaonkar, P. P. (Australian Journal of Chemistry, 2007)
An anhydrous magnesium sulfate mediated solvent-free protocol is described for the synthesis of dihydropyrimidinones (Biginelli compounds) at ambient temperature.

Sulfamic acid: an efficient and cost-effective solid acid catalyst for the synthesis of alpha-aminophosphonates at ambient temperature - Mitragotri, Satish D.; Pore, D. M.; Desai, Uday V.; Wadgaonkar, P. P. (Catalysis Communications, 2008)
Sulfamic acid catalyzed solvent-free protocol has been developed for the synthesis of alpha-aminophosphonates by three component condensation between aldehydes, amines and diethyl phosphite at ambient temperature. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: alpha-Aminophosphonates; diethylphosphite (DEP); solid acid catalyst; Solvent-free; sulfamic acid (SA)